"Food aid is killing Himalayan farms". Debunking the false dependency narrative in Karnali, Nepal. (April 2019) - Gautam, Yograj
Highlights: Food aid is considered to create 'dependency ' in Himalayan farming communities. Dependency is explained in terms of "rice based diets " and neglect of local farming. Empirical evidence run contrary to the dependency narrative. The dietary pattern is well embedded with locally grown traditional grains. Food aid can provide effective safety net to farmers against environmental and socio-economic stresses. Abstract: Food aid constitutes a heated debate in development discourse. In Nepal's Himalayan region, it is blamed for aggravating food insecurity by inducing dependency and negatively affecting local agriculture and diet patterns. Transferring large amount of rice, a grain scantily produced locally, food aid is considered to have worsened human nutrition by directing the traditionally diverse diet to rice-based monotonous diet. The aid dependent farmers are alleged to have given up cultivating land for less preferred local grains, ultimately reducing local food production and reproducing the need for more aid. Therefore, the removal of food aid is considered indispensable to the achievement of self-sustained food security. This paper examines the dependency narrative in light of empirical data produced by a mixed-method study conducted in Humla, a highly food insecure district in western Nepal. The results show no indication of 'dependency' as alleged in the narrative. Despite the free/concessional food transfers, the local farms have not only maintained diverse traditional crops, recent agricultural innovation has actually increased on-farm crop diversity. On average, the local grains contribute about 65% of the total local consumption signifying a diet pattern well embedded with the local food system. Food aid transfers cover about 20% of the total food need and constitute an important resource for households suffering high food scarcity. Therefore, we argue that the idea of removing food aid in the guise of "dependency" will directly affect many poor farmers' food access, and will also leave an increased number of Himalayan farmers vulnerable to food insecurity in the face of emerging environmental and socio-economic stresses.